2001
DOI: 10.1177/030089160108700612
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo Biloba Extract (Egb 761) Modulates Bleomycin-induced Acute Lung Injury in Rats

Abstract: The effect of Ginkgo biloba extract (EGb 761) on bleomycin (BLM)-induced acute lung injury was studied in rats. The responsiveness of isolated pulmonary arterial rings to 5-hydroxytryptamine (5-HT) as well as the levels of some relevant biochemical markers in the lung tissue were taken as evidence for the acute lung injury. BLM was given intraperitoneally at a dose of 15 mg/kg/day for five consecutive days. It was found that BLM treatment attenuated the vasoconstrictor effect of 5-HT on the isolated pulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…These data are in good agreement with Daba et al (2002). El-Khatib et al (2001) demonstrated that bleomycin in lung tissues increased the level of lipid peroxides and enhanced the activity of GSH-Px. In our data, GSH-Px activity in plasma was unchanged after bleomycin treatment.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These data are in good agreement with Daba et al (2002). El-Khatib et al (2001) demonstrated that bleomycin in lung tissues increased the level of lipid peroxides and enhanced the activity of GSH-Px. In our data, GSH-Px activity in plasma was unchanged after bleomycin treatment.…”
Section: Discussionsupporting
confidence: 90%
“…Oxidative stress plays an important role in the development of fibrotic responses in the lung. Recent studies demonstrated that Ginkgo biloba treatment in rats improved lung fibrosis induced by bleomycin (El-Khatib et al, 2001;Daba et al, 2002). However, it is not clear whether plasma oxidant and anti-oxidant systems play a role in pulmonary fibrosis induced by bleomycin.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, lazaroids are protective against bleomycin-induced lung fibrosis in rats (49,132). A number of natural products that contain polyphenolic compounds, such as Ginko biloba extracts and curcumin, have been found to suppress lung oxidative stress and fibrosis in rats treated with bleomycin (48,67,93,152,207).…”
Section: Fibrogenic Drugs Antioxidants and Oxidative Stressmentioning
confidence: 99%
“…In a bleomycin-induced acute lung injury rat model, a G. biloba leaf extract (EGb 761) reduced the responsiveness and diminished the occurrence of further reduction in the vasoconstrictor response of the pulmonary artery due to 5-hydroxytryptamine (5-HT). Furthermore, EGb 761 normalized bleomycin-induced alterations in the measured lung tissue biochemical markers [68]. Additionally, in another study, EGb 761 reduced protein leakage, neutrophil infiltration, myeloperoxidase (MPO, a heme enzyme present in the primary granules of neutrophils), and metalloproteinase (MMP)-9 activities in an LPS-initiated ALI rat model.…”
Section: Introductionmentioning
confidence: 99%